Gestational diabetes complicated with preterm birth: a retrospective cohort study - Shuyao Huang; Yanni Guo; Xia Xu; Lingling Jiang; Jianying Yan (BMC, 2024)
Abstract Objective To delineate the clinical characteristics of preterm birth (PTB) in the context of gestational diabetes mellitus (GDM). Methods A retrospective cohort study was conducted, including 14,314 pregnant women with GDM who delivered at Fujian Provincial Maternity and Children's Hospital from January 1, 2018, to December 31, 2021. PTB was stratified into late PTB (34-36 weeks of gestation) and early PTB (< 34 weeks) and pregnancy complications were analyzed. Results Compared to the term birth (TB) cohort, a higher prevalence of premature rupture of membranes, hypertensive diseases of pregnancy (HDP), intrahepatic cholestasis of pregnancy (ICP), anemia and cervical insufficiency was observed in the PTB cohort. Notably, early PTB increased the incidence of HDP, ICP, anemia and cervical insufficiency compared to late PTB. In the early stages of pregnancy, early PTB was characterized by elevated triglyceride (TG) levels and decreased high-density lipoprotein cholesterol (HDL-C) levels compared to late PTB. In the late pregnancy stages, early PTB was associated with increased white blood cell (WBC) and neutrophil counts. No disparities were observed in 75 g oral glucose tolerance test (OGTT) between early and late PTB. Conclusion Enhanced surveillance and management of GDM, particularly in the presence of HDP, ICP and anemia, are imperative to mitigate the risk of PTB. The lipid profile may serve as a predictive tool for early PTB in the early stages of pregnancy, warranting further studies.